Inflammatory Markers: C-Reactive Protein, Erythrocyte Sedimentation Rate, and Leukocyte Count in Vitamin D Deficient Patients with and without Chronic Kidney Disease. (25th June 2013) - Yildirim, Ibrahim; Hur, Ender; Kokturk, Furuzan
Abstract : Although some studies revealed a positive relationship between vitamin D3 deficiency and inflammatory markers, there have been also many studies that failed to find this relationship. The aim of this large scaled study is to determine the association between the level of plasma 25 hydroxy vitamin D3 [25-(OH) D3 ] and inflammatory markers in the general population without chronic kidney disease (CKD) and in patients with CKD. Participants with simultaneously measured inflammatory markers and 25-(OH) D3 levels were retrospectively analyzed (n = 1897 ). The incidence of all-cause inflammation infection, hospitalization, chronic renal failure, and vitamin B12 deficiency was evaluated. The medians of serum creatinine levels in subjects without renal failure were lower in 25-(OH) D3 deficient group. Patients with CKD were more likely to have vitamin D3 deficiency compared with normal GFR. 25-(OH) D3 levels were associated with a greater incidence of all-cause hospitalization, hypoalbuminemia, and vitamin B12 deficiency. However, there was no relationship between inflammatory markers and vitamin D3 levels. In 25-(OH) D3 deficient patients, inflammatory markers can be related to other inflammatory and infectious status such as malnutrition and cachexia. We believed that there must be a relationship between vitamin deficiency and inflammatory markers due to other causes than low 25-(OH) D3 status.